Development of heterogeneous catalysts based on porous silica material and lanthanide ions for the hydrolysis of phopsphodiesters - Carlos Alberto Amaya Vargas (2019)
Silica is abundant and structurally malleable for numerous applications. In this work, we applied mesoporous silica and its functionalized forms for catalysis of phosphodiester hydrolysis. Hybrid materials were obtained by post-grafting with carboxyl and amine groups, which wereanchor points for lanthanide (III) ions. Materials were characterized regard their composition, morphology and properties using infrared spectroscopy, thermo gravimetric analysis (TGA), differential scanning calorimetry (DSC), elemental analysis, total-reflection X-ray fluorescence(TXRF), nitrogen adsorption, scanning and transmission electron microscopy, X-ray powder diffraction (XRD), and zeta potential. Functionalization and coordination were effective, and the hybrid material kept the mesoporous structure with small surface area reduction. Theorganometallic silica was an effective heterogeneous catalyst for the hydrolysis of the prototypical phosphodiester bis(2,4-dinitrophenyl)phosphate at different pH and 25°C. In thefirst use the catalytic proficiencies were between 10 to 50-fold relative to the uncatalyzed hydrolysis. All materials showed higher catalytic activity upon hydrated reuse, which was caused by structural changes on the silica surface. The reuse of PSiM-NH2La on hydrated conditions atpH 8.1 followed a first-order rate constant with kobs = 8.4 x 10-3 min-1, corresponding to a catalytic proficiency of about 600-fold. We observed that hydration (and the hydration method) of the surface is fundamental for the catalytic properties of the material. The complete hydrolysis doesnot follow a simple two consecutive first-order kinetics, and we used a model that takes into account the Avrami kinetic model, which describes how solids transform from one phase (state of matter) to another at constant temperature. The phase change was characterized by X-raypowder diffraction, nitrogen adsorption, transmission electron microscopy, zeta potential, and solid-state nuclear magnetic resonance. The importance of the nature of functionalization (carboxyl and amino) was evaluated in different pH showing that BDNPP hydrolysis isaccomplished in different ways but with similar catalytic proficiencies.